Biometrics electronic purse - Abdul Rahman, Abdul Wahab; Eng, Chong Tan; S., M. Heng (1999)
This paper propose an eflcient and universal Smart Card System to be implemented for banking applications over the Internet to support the fast growing Electronic Commerce Industry. Encryption technology, such as Digital Certlficate and Signature, were exploited and integrated with other authentication speclfication (e.g. SET) to provide secure transactions over a distributed network. A simple PIN code verlfication is no longer suflcient and would require a more complex and fools proof authentication method. A 56-bit DES encryption algorithm can easily be broken in just 2 to 3 days using the EFF DES CRACKER, an unclassified ASIC machine. This paper looked into using biometrics as a mean of authentication, thus requiring a new generation of Smart Card technology to be implemented in banking and multiple applications environment. A proto-type of the proposed Biometrics Electronic Purse (BEP) was build using the Schlumberger Cyberflex Multi8K Java Card with a simple File Management Utilities software to upload download biometrics template to/&om the Java Card.